Hydration and nutrition care practices in stroke: findings from the UK and Australia - Colette Miller; Stephanie P. Jones; Munirah Bangee; Cintia Mayel Martinez-Garduno; Marian C. Brady; Dominique A. Cadilhac; Simeon Dale; Elizabeth McInnes; Sandy Middleton; Caroline L. Watkins; C. Elizabeth Lightbody (BMC, 2023)
Abstract Background Dehydration and malnutrition are common in hospitalised patients following stroke leading to poor outcomes including increased mortality. Little is known about hydration and nutrition care practices in hospital to avoid dehydration or malnutrition, and how these practices vary in different countries. This study sought to capture how the hydration and nutrition needs of patients' post-stroke are assessed and managed in the United Kingdom (UK) and Australia (AUS). Aim To examine and compare current in-hospital hydration and nutrition care practice for patients with stroke in the UK and Australia. Methods A cross-sectional survey was conducted between April and November 2019. Questionnaires were mailed to stroke specialist nurses in UK and Australian hospitals providing post-stroke inpatient acute care or rehabilitation. Non-respondents were contacted up to five times. Results We received 150/174 (86%) completed surveys from hospitals in the UK, and 120/162 (74%) in Australia. Of the 270 responding hospitals, 96% reported undertaking assessment of hydration status during an admission, with nurses most likely to complete assessments (85%). The most common methods of admission assessment were visual assessment of the patient (UK 62%; AUS 58%), weight (UK 52%; AUS 52%), and body mass index (UK 47%; AUS 42%). Almost all (99%) sites reported that nutrition status was assessed at some point during admission, and these were mainly completed by nurses (91%). Use of standardised nutrition screening tools were more common in the UK (91%) than Australia (60%). Similar proportions of hydration management decisions were made by physicians (UK 84%; AUS 83%), and nutrition management decisions by dietitians (UK 98%; AUS 97%). Conclusion Despite broadly similar hydration and nutrition care practices after stroke in the UK and Australia, some variability was identified. Although nutrition assessment was more often informed by structured screening tools, the routine assessment of hydration was generally not. Nurses were responsible for assessment and monitoring, while dietitians and physicians undertook decision-making regarding management. Hydration care could be improved through the development of standardised assessment tools. This study highlights the need for increased implementation and use of evidence-based protocols in stroke hydration and nutrition care to improve patient outcomes.